2020
DOI: 10.1038/s41598-020-65004-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of proton-transfer coupled rotations in ATP synthase FO motor

Abstract: the f o motor in f o f 1 Atp synthase rotates its rotor driven by the proton motive force. While earlier studies elucidated basic mechanisms therein, recent advances in high-resolution cryo-electron microscopy enabled to investigate proton-transfer coupled F o rotary dynamics at structural details. Here, taking a hybrid Monte Carlo/molecular dynamics simulation method, we studied reversible dynamics of a yeast mitochondrial f o. We obtained the 36°-stepwise rotations of F o per one proton transfer in the ATP s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 50 publications
3
49
1
Order By: Relevance
“…In kinetic simulations involving transitions between the states, the Gillespie algorithm is often used ( 63 ). In the present study, explicit stochastic simulations of the GTPase cycle were, however, carried out, because most of the computer time was already needed for integrating the equations of motion for the membrane and the beads.…”
Section: Methodsmentioning
confidence: 99%
“…In kinetic simulations involving transitions between the states, the Gillespie algorithm is often used ( 63 ). In the present study, explicit stochastic simulations of the GTPase cycle were, however, carried out, because most of the computer time was already needed for integrating the equations of motion for the membrane and the beads.…”
Section: Methodsmentioning
confidence: 99%
“… 26 28 By determining the free energy landscapes using a coarse-grained model, Bai and Warshel have recently shown that this simple electrostatic view of the F o directionality only holds if the energetics of proton transfer to the carboxylates is included, ensuring the asymmetric attraction between Arg and the R and B sites. 13 , 29 , 30 …”
mentioning
confidence: 99%
“…MD simulations of the F 1 subcomplex have provided insight into the transfer of mechanical energy by applying rotations on the γ subunit [ 159 , 160 ]. Simulations of the c 10 ring of the F 0 subcomplex provided insight into the proton binding mechanism [ 161 , 162 ]. Several simulations of the F 0 motor investigated the ATP synthase’s relation to MPTP.…”
Section: Computational Modeling Of Mitochondria In Brain Disordersmentioning
confidence: 99%